Do parents’ mindsets matter?: implicit theories and co-regulation in preschoolers’ self-regulation - Stern, Maren (2022)
Parents and their co-regulatory behaviors play a fundamental role in the development of child self-regulation. Concurrently, influencing factors that explain differences in parents’ behavior are insufficiently understood. Implicit theories of individuals are known to significantly determine behavior, motivation, and cognition in several domains. While implicit theories of students have been frequently studied, little research exists on implicit theories of parents. Therefore, the present dissertation aims to examine parents’ implicit theories in co- and self-regulatory processes in preschoolers. To this end, a theoretical framework is introduced that integrates the SOMA (setting/operating/monitoring/achievement) model by Burnette et al. (2013) and the three-term standard model by Bornstein et al. (2018). This dissertation presents three empirical papers that explore parents’ implicit theories and the interplay of co- and self-regulatory processes. Paper 1 is based on an online survey and examines how different domains of implicit theories co-occur within parents and are related to demographics, parents’ attitudes, and co-regulatory strategies. Three belief profiles with different configurations across domains emerge. Entity theorists have the lowest educational background. Incremental self-regulation theorists report more failure-is-enhancing mindsets, less performance-avoidance goals, and more mastery-oriented strategies than parents in the other profiles. Paper 2 uses an integrative theoretical framework to analyze different aspects of mothers’ scaffolding in mother-child interactions during a problem-solving task. The findings suggest that mothers apply different scaffolding strategies that may enhance children’s metacognitive self-regulatory strategies and task performance. Paper 3 evaluates the effects of mothers’ implicit theories in an experimental investigation with six conditions (intelligence-is-malleable, intelligence-is-stable, failure-is-enhancing, failure-is-debilitating, self-regulation-is-malleable, self-regulation-is-stable). The results indicate that parenting behaviors differ in dependence of the study condition. Mothers’ implicit theories indirectly affect children’s self-regulatory strategies, mediated via parenting behaviors. In conclusion, this dissertation provides further insight into (1) parents’ implicit theories in preschoolers, (2) the domain-specificity and interplay of different domains of implicit theories, (3) the theoretical framework of mothers’ scaffolding when studying mother-child interactions, and (4) the development of the SOMA model. The present work offers practical implications for parenting interventions and new avenues for future research.
Keywords: Hochschulschrift